An Intensified Esterification Process of Palm Oil Fatty Acid Distillate Catalyzed by Delipidated Rice Bran Lipase - Fui Chin Chong; Beng Ti Tey; Zanariah Mohd. Dom; Nordin Ibrahim; Russly Abd. Rahman; Tau Chuan Ling (The Scientific World Journal)
An intensified esterification process was operated by circulating 10 l of reaction mixtures, consisting of palm oil fatty acid distillate (PFAD) and glycerol in hexane, through a packed-bed reactor (PBR) filled with 10 kg of delipidated rice bran lipase (RBL). The influence of the process parameters, such as reaction temperature and type of water-removal agent, on the performance of this intensified esterification process were investigated. The highest degree of esterification (61%) was achieved at a reaction temperature of 65°C, using silica gels as the water-removal agent. Thin-layer chromatography (TLC) analysis showed that the major composition of the esterified product was diacylglycerol.